THE RELATION OF THE SACRED IN CAPOEIRA GAME (Fiep Bulletin - online, 2014)
The aim of this study is to discuss aspects of the sacredness in capoeira game so as to contribute to the understanding of some symbolic plots which constitute this element of the body culture of movement. Capoeira relies on religiosity as one of the pillars of its social imaginary. Berimbau and atabaque lend their sacred attributes and are worshiped in the circle, its chants tell stories and legends of Gods and Orixás which, along with Catholicism, comprise the syncretism of a religiosity peculiar to the Africans' cultural manifestations and its descendants in Brazil.
Keywords: capoeira; sacredness; social imaginary